Mechanical Behavior of Carbide-Free Medium Carbon Bainitic Steel - ZHANG, XIAOXU (My University, 2016)
Carbide-free bainitic (CFB) steels have gained increasing attention in recent years because of their excellent mechanical properties. The excellent combination of strength, ductility and toughness achieved in these steels is only matched by that of Maraging steels which cost 10 to 100 more than the carbide-free bainitic steels. The excellent mechanical behavior of CFB steel is mainly due its complex microstructure (bainitic ferrite, retained austenite and martensite) consisting of a high strength phase (ultra fine bainitic ferrite) and TRIP effect from retained austenite. Carbide formation is avoided due to high silicon content which suppresses cementite precipitation from austenite. The effect of bainitic transformation time on the microstructure and mechanical properties was investigated in a steel containing 0.4%C-2.8%Mn-1.8%Si. The microstructure was characterized using optical and transmission electron microscopy; it consisted of bainitic ferrite, martensite and retained austenite. This microstructure exhibited an extended elasto-plastic transition leading to very high initial work hardening rates. The work-hardening behavior was investigated in detail using strain-path reversals to measure the back-stresses. These measurements point to a kinematic hardening due to the mechanical contrast between the microstructural constituents. The strain aging effect at room temperature on the CFB steel was also been analyzed in great detail. The static strain aging effect at room temperature can not be overlooked in the carbide free bainitic steel. After isothermal bainite heat treatment, the yield strength of the material is increased by about 80MPa, and the ultimate tensile strength is improved by more than 100MPa after aging at room temperature for one week. This phenomenum could be related to the interactions between carbon atoms and the dislocations, grain boundaries and the redisual stresses. Examination of the fracture surfaces indicated that the prior austenite grain boundaries play an important role in the fracture process. A set of experiments were designed to study the effect of ausforming on the microstructure and mechanical properties of CFB steels. Based on its mechanical behavior under tensile tests and microstructural analysis by EBSD, the TRIP effect was contributing to the work hardening behavior. The changes in morphology and variant selection of the bainitic ferrite lath in the ausformed carbide free bainitic steel were also observed. A new set of chemistry was design with reduced carbon and manganese content to further improve the weldability and the reproducibility of the carbide free bainitic steel.
Keywords: CARBIDE FREE BAINITIC STEEL; MECHANICAL PROPERTY